A Method to Detect and Classify Inconsistencies of Moving Objects’ Stops with Requested and Reported Tasks - da Silva, Felipe Pinto; Fileto, Renato (Journal of Information and Data Management, 2015)
Moving objects’ trajectories automatically collected by using sensors enable tracking objects doing activities in the geographic space. However, methods for analyzing trajectories rarely compare them to tasks execution plans and/or travel diaries. This article proposes a method to detect and classify inconsistencies of trajectories with both planned tasks and reported tasks, by checking their spatial and temporal incompatibilities. The classified inconsistencies returned help to investigate possible problems on tasks planning or reporting, and even misbehaviors of moving objects. This method has been implemented in a prototype on top of PostGIS, and helped to detect and investigate a variety of inconsistencies in real data provided by a water supply company.